Seasonal forecast skill for extratropical cyclones and windstorms - Befort, Daniel J.; Wild, Simon; Knight, Jeff R.; Lockwood, Julia F.; Thornton, Hazel E.; Hermanson, Leon; Bett, Philip E.; Weisheimer, Antje; Leckebusch, Gregor C. (Quarterly journal of the Royal Meteorological Society, 2019)
Extratropical cyclones and their associated extreme wind speeds are a major cause of vast damage and large insured losses in several European countries. Reliable seasonal predictions of severe extratropical winter cyclones and associated windstorms would thus have great social and economic benefits, especially in the insurance sector. We analyse the climatological representation and assess the seasonal prediction skill of wintertime extratropical cyclones and windstorms in three multi‐member seasonal prediction systems: ECMWF‐System3, ECMWF‐System4 and Met Office‐GloSea5, based on hindcasts over a 20‐year period (1992–2011). Small to moderate positive skill in forecasting the winter frequency of extratropical cyclones and windstorms is found over most of the Northern Hemisphere. The skill is highest for extratropical cyclones at the downstream end of the Pacific storm track and for windstorms at the downstream end of the Atlantic storm track. We also assess the forecast skill of windstorm frequency by using the North Atlantic Oscillation (NAO) as the predictor. Prediction skill improves when using this technique over parts of the British Isles and North Sea in GloSea5 and ECMWF‐System4, but reduces over central western Europe. This suggests that using the NAO is a simple and effective method for predicting windstorm frequency, but that increased forecast skill can be achieved in some regions by identifying windstorms directly using an objective tracking algorithm. Consequently, in addition to the large‐scale influence of the NAO, other factors may contribute to the predictability of windstorm frequency seen in existing forecast suites, across impact‐relevant regions of Europe. Overall, this study reveals for the first time significant skill in forecasting the winter frequency of high‐impact windstorms ahead of the season in regions that are vulnerable to such events. In this study, the skill of three state‐of‐the‐art seasonal prediction systems is analysed for Northern Hemisphere extratropical windstorm and cyclone events. Results show significant skill for the eastern Atlantic/central Europe in the latest two systems (see Figure showing rank coefficients of annual track densities for windstorms). Furthermore, using the North Atlantic Oscillation (NAO) as predictor for windstorm activity adds some value over northern Europe but for large areas over Europe using the full model information is superior.